The death of public school : how conservatives won the war over education in America - Fitzpatrick, Cara (Basic Books, 2023)
"Conservatives have succeeded in establishing their vision of education in America, one in which government funds can be used to pay for both public and private schools. As a result, the very meaning of public education in the United States has shifted away from the idea of a universal good. To understand how we got here, The Death of Public School argues, we must look back at the turbulent history of school choice. The Death of Public School tells the rich and surprising story about the people, unusual political alliances, and philanthropic interests that have fueled the rise of the school choice movement over the last 70 years. Drawing on two decades of experience as an education reporter, Fitzpatrick traces the origins of school choice in the modern era from Milton Friedman, a Nobel Prize-winning economist who helped lead a revival of conservatism in the 20th century, to the present day, in which conservatives are propelling the spread of choice options, such as charter schools, school vouchers, and tax-credit scholarships. Fitzpatrick paints rich portraits of people from various political and cultural backgrounds--from free-market conservatives to Catholic priests to white segregationists in the South to Black parents in urban school systems--who, in pursuit of their vision of education, linked arms with individuals across the aisle"--